Effect of glutathione addition at harvest on Sauvignon Blanc wines. (14th April 2021) - Lyu, X.; Del Prado, D.R.; Araujo, L.D.; Quek, S.‐Y.; Kilmartin, P.A.
Abstract: Background and Aims: Polyfunctional mercaptans, such as 3‐mercaptohexanol and 3‐mercaptohexyl acetate, produce passion‐fruit, tropical and stalky aromas in white wines such as Vitis vinifera L. Sauvignon Blanc. Oxidation processes, however, can be detrimental to the formation and stability of these desirable thiol compounds. The use of antioxidants during winemaking is most important to protect polyfunctional mercaptans from oxidation, starting at grape harvest. Trials were undertaken at harvest with the addition of glutathione (GSH) alone or with further additives. Methods and Results: The addition of GSH along with sulfur dioxide to the juices increased the concentration of polyfunctional mercaptans in the finished wines, and more so when ascorbic acid was also included. The addition of inactivated yeast products, however, applied early to the fruit at harvest, had little effect on wine GSH concentration or on the formation of polyfunctional mercaptans. Few differences were observed with other wine aroma families following antioxidant addition at harvest. Conclusions: Glutathione as an antioxidant added at harvest protected against juice oxidation and increased the concentration of polyfunctional mercaptans in the finished wines. Significance of the Study: This study has demonstrated a positive benefit to the formation of polyfunctional mercaptans with passion‐fruit/tropical aromas, from the addition of GSH at harvest. The GSH additions could be used with lower sulfite application but still create wines with high 3‐mercaptohexanol/3‐mercaptohexyl acetate characters.